Observation of the protein expression level via naked eye: Pt clusters catalyze non-color molecules into brown-colored molecules in cells - Xia, Dongfang; Zhang, Yong; Zhang, Chunyu; Yao, Xiuxiu; Tang, Yuhua; Wang, Fuchao; Han, Xu; Yin, Hongzong; Xu, Chao; Gao, Xueyun (Frontiers in Chemistry, 2023)
αvβ3 is overexpressed in various tumor cells and plays a key role in tumor genesis, invasion, and metastasis. Therefore, it is of great significance to precisely detect the αvβ3 level in cells via a simple method. For this purpose, we have constructed a peptide-coated platinum (Pt) cluster. Due to its bright fluorescence, well-defined Pt atom numbers, and peroxidase-like catalytic activity, this cluster can be used to evaluate αvβ3 levels in cells by fluorescence imaging, inductively coupled plasma mass spectrometry (ICP-MS), and catalytic amplification of visual dyes, respectively. In this report, the expression level of αvβ3 in living cells is well-detected by the naked eye under an ordinary light microscope when the Pt cluster binds to αvβ3 in cells and catalyzes non-color 3,3′-diaminobenzidine (DAB) into brown-colored molecules in situ. Moreover, SiHa, HeLa, and 16HBE cell lines with different αvβ3 expression levels can be visually distinguished by the peroxidase-like Pt clusters. This research will provide a reliable method for the simple detection of αvβ3 levels in cells.